2014
DOI: 10.5507/bp.2012.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of progesterone-carbachol derivative on perfusion pressure and coronary resistance in isolated rat heart: via activation of the M<sub>2</sub> muscarinic receptor

Abstract: Aim. The present study was designed to investigate the effects of progesterone-carbachol derivative on perfusion pressure and coronary resistance in rats. An additional aim was to identify the molecular mechanisms involved. Methods. The Langendorff model was used to measure perfusion pressure and coronary resistance changes in isolated rat heart after progesterone-carbachol derivative alone and after the following compounds; mifepristone (progesterone receptor blocker), yohimbine (α 2 adreno-receptor antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The results showed that the effect of estradiol derivative was not inhibited by yohimbine or ICI 118,551, indicating that the molecular mechanism involved is not through adrenergic activity. Analyzing these results and other reports which indicate that some steroid derivatives induces activation of M 2 muscarinic (Figueroa-Valverde et al, 2012) that induces consequently a negative inotropic response and low blood pressure by activation of nitric oxide synthase (NOS) and increased production of cyclic GMP. In this study, the activity of estradiol derivative on left ventricular pressure was evaluated in the absence or presence of atropine.…”
Section: Discussionsupporting
confidence: 55%
“…The results showed that the effect of estradiol derivative was not inhibited by yohimbine or ICI 118,551, indicating that the molecular mechanism involved is not through adrenergic activity. Analyzing these results and other reports which indicate that some steroid derivatives induces activation of M 2 muscarinic (Figueroa-Valverde et al, 2012) that induces consequently a negative inotropic response and low blood pressure by activation of nitric oxide synthase (NOS) and increased production of cyclic GMP. In this study, the activity of estradiol derivative on left ventricular pressure was evaluated in the absence or presence of atropine.…”
Section: Discussionsupporting
confidence: 55%
“…Doses of ACh and SNP were determined according to previous research (Mourmoura et al 2014). The coronary resistance was determined by the relationship between coronary flow and perfusion pressure (mm Hg/mL/min) (Figueroa-Valverde et al 2012).…”
Section: Coronary Resistancementioning
confidence: 99%
“…The effects were obtained in isolated hearts perfused at a constant flow rate of 10 ml/min. Since a constant flow was used, changes in coronary pressure reflected the changes in coronary resistance (Figueroa-Valverde et al, 2012).…”
Section: Evaluation Of Effects Exerted By the Progesterone Derivativementioning
confidence: 99%
“…Recently, a study indicated that a progesterone derivative induce acardioprotective effect on injury by ischaemia/reperfusion via M2 muscarinic receptor and activation of nitric oxide synthase in an animal model (Figueroa-Valverde et al, 2012). Nevertheless, there are reports which indicate that the administration of medroxyprogesterone acetate can inhibit the effects of estradiol that lead to protection of the myocardium from reperfusion injury and that this involves both neutrophildependent and neutrophil-independent mechanisms (Jeanes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%